2018
DOI: 10.15605/jafes.033.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemia among Insulin-Treated Patients with Diabetes: Southeast Asia Cohort of IO HAT Study

Abstract: Objective: To provide real-world data on hypoglycaemia incidence in patients with type 1 (T1D) or type 2 diabetes (T2D) from the Southeast Asian cohort of the International Operations Hypoglycaemia Assessment Tool (IO HAT) study.Methodology: IO HAT was a non-interventional, multicentre, 6-month retrospective and 4-week prospective study of hypoglycaemic events among insulin-treated adults with T1D or T2D, including four countries in Southeast Asia (Singapore, Philippines, Indonesia, and Bangladesh). Data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This study was in line with 50% of the RECAP-DM study in Argentina (35). This finding was lower than 86.7% in Debre Markos Referral Hospital (5), 88% in Tikur Anbessa Specialized Hospital (23), and 94.3% in St. Paul's Hospital Millennium Medical College (22) studies in Ethiopia and 91.7% from HAT study in Brazil (36), 97.1% in Colombia (37), 97.4% from an international survey in nine countries (38), and 100% from the Southeast Asia cohort of IO HAT study (39). The variation observed between this and other studies may be due to the operational definition used.…”
Section: Discussionmentioning
confidence: 86%
“…This study was in line with 50% of the RECAP-DM study in Argentina (35). This finding was lower than 86.7% in Debre Markos Referral Hospital (5), 88% in Tikur Anbessa Specialized Hospital (23), and 94.3% in St. Paul's Hospital Millennium Medical College (22) studies in Ethiopia and 91.7% from HAT study in Brazil (36), 97.1% in Colombia (37), 97.4% from an international survey in nine countries (38), and 100% from the Southeast Asia cohort of IO HAT study (39). The variation observed between this and other studies may be due to the operational definition used.…”
Section: Discussionmentioning
confidence: 86%
“…Abstract and title screening excluded 12,096 records, and full‐text screening eliminated 460 records, leaving 15 studies 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 that satisfied inclusion criteria. Backward and forward citation searches of these studies identified 3 additional studies, 35 , 36 , 37 and hand searches identified 2 studies, 38 , 39 resulting in 20 total studies selected for extraction and synthesis (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies assessed impairment in the workplace among participants from Eastern Europe 23 and Southeast Asia. 38 Over a 30‐day period, approximately 3% of adults with type 2 diabetes reported having been absent from work, and 2%–5% reported having left work early, as a direct consequence of hypoglycaemia. Impairment during non‐work activities (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations